Pengaruh Media Dua Dimensi Terhadap Pemahaman Konsep Matematika - Wika Haryanti; Adisel Adisel; Fatrima Santri Syafir; Suryati Suryati (Journal of Elementary School (JOES), 2021)
The purpose of this study was to determine the effect of two-dimensional media on the understanding of mathematical concepts in the fourth grade students of SD Negeri 09 Seluma. This research is a quantitative study on the effect of two-dimensional media on understanding the concept of Mathematics in the fourth grade students of SD Negeri 09 Seluma. Data collection techniques used in this study were observation, tests and documentation. Data analysis techniques used are data analysis requirements test and hypothesis testing. The data analysis technique consisted of normality test, homogeneity test, t-test. This can be seen from the t-test value of -4.228 with P of 0.001 because the P value <0.05 which means the working hypothesis (Ha) in this study is accepted, namely there is a difference between the use of two-dimensional media on the understanding of Mathematics concepts for fourth grade elementary school students. Country 09 Seluma. It was concluded that two-dimensional media had an influence on understanding the concept of mathematics. Keywords: Media, Two Dimensions, Concepts, Mathematics.